2009
DOI: 10.1080/02701367.2009.10599558
|View full text |Cite
|
Sign up to set email alerts
|

Desaturation Patterns Detected by Oximetry in a Large Population of Athletes

Abstract: Optimal exercise performance in well trained athletes can be affected by arterial oxygen saturation failure. Noninvasive detection of this phenomenon when performing a routine ergometric test can be a valuable tool for subsequent planning of the athlete's training recovery, and nutrition. Oximetry has been used to this end. The authors studied 339 athletes performing a similar exercise trial under well controlled environmental conditions. Maximum speed, oxygen uptake, and heart rate levels were simultaneously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…These walktest results are similar to the athlete treadmill results 34 in that (1) is steady like (a), (2) is decline like (e) with a bit of recovery like (d), and (3) is abrupt at the end like (f) with the progressive decline of (b). There is no chronic analogue to pattern (c) where the decline is only transient and the recovery is complete to the normal level.…”
Section: Oxygen Saturation Patternssupporting
confidence: 84%
See 2 more Smart Citations
“…These walktest results are similar to the athlete treadmill results 34 in that (1) is steady like (a), (2) is decline like (e) with a bit of recovery like (d), and (3) is abrupt at the end like (f) with the progressive decline of (b). There is no chronic analogue to pattern (c) where the decline is only transient and the recovery is complete to the normal level.…”
Section: Oxygen Saturation Patternssupporting
confidence: 84%
“…In some kinesiology studies with healthy athletes, different oxygen desaturation patterns were observed 34 representing different health status depending on physiological conditions. The 339 athletes tested on treadmills displayed 6 saturation patterns: The continuous records of oxygen saturation with pulmonary patients during 6MWT exhibited similar patterns to these athletes, although the range of saturation values was lower due to lower fitness and the desaturation occurred more quickly.…”
Section: Oxygen Saturation Patternsmentioning
confidence: 98%
See 1 more Smart Citation
“…The criteria were based on VO 2 plateau, HR, BLC, RER, oxygen saturation and RPE. O 2 saturation was included because of recent research indicating that many athletes experience exercise induced arterial hypoxemia at VO 2 peak (15). Oxygen saturation is a simple and inexpensive measurement that is non-invasive which makes it an attractive criterion for researchers to use.…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…The fingertip pulse oximeter can use for measuring heart rate and oxygen saturation to examine athlete's training recovery [36] . This study was designed to use the fingertip pulse oximeter (Model: MD300C2, ver4.0C2, China) ranging from 70 -99% (±3%) to measure participants' heart rate during imagery training.…”
Section: The Physical and Psychological State Measure In Sports With mentioning
confidence: 99%